Empowering Communities through Psychoeducational Outreach to Support Elementary Students' Academic Success - Prameswari Naila Putri, Zahra; Laeli, Sobrul (LPPM Universitas Jambi, 2024)
This community service program aimed to enhance primary school teachers' understanding of students' psychological development and its impact on academic achievement. The program provided psychoeducational workshops and mentoring sessions for teachers in rural schools in Jambi, Indonesia. By integrating psychological principles into teaching practices, teachers learned to identify individual differences, address emotional challenges, and improve classroom management. The results showed increased teacher confidence and better adaptation of teaching strategies to meet students' developmental needs. Teachers also reported improved classroom dynamics and academic performance of students. The program highlights the importance of empowering educators with educational psychology to enhance both teaching quality and student well-being. It suggests that similar community-based psychoeducational initiatives should be scaled up to benefit more educators, especially in underserved areas.